1977
DOI: 10.1002/apmc.1977.050580104
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an kautschukmodifiziertem PVC

Abstract: ZUSAMMENFASSUNG:An Mischungen verschiedener Pfropfkautschuke auf ABS-, MBS-und AMBS-Basis rnit PVC werden die Beziehungen zwischen chemischer Zusammensetzung, morphologischem Aufbau und Eigenschaften untersucht. Mit steigendem Pfropfungsgrad lassen sich die Pfropfkautschuke besser in PVC dispergieren, und der WeiBbruch der Mischungen verringert sich unter gleichzeitiger Abnahme der Schlagzahigkeit. Die besten Eigenschaften erhalt man bei einer KautschukteilchengroBe von etwa 200 nm; die chemische Zusammensetzu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…For ABS, it is well known that the deformation mechanisms include crazing [33, 34], shear yielding [35], cavitiation of rubber particles, and the induced yielding in matrix [36]. Combining the results of TEM and SEM obtained here, it is found that craze, cavitation of rubber particles, and the induced shear yielding in SAN matrix coexist in ABS‐L blend under impact condition.…”
Section: Resultssupporting
confidence: 60%
“…For ABS, it is well known that the deformation mechanisms include crazing [33, 34], shear yielding [35], cavitiation of rubber particles, and the induced yielding in matrix [36]. Combining the results of TEM and SEM obtained here, it is found that craze, cavitation of rubber particles, and the induced shear yielding in SAN matrix coexist in ABS‐L blend under impact condition.…”
Section: Resultssupporting
confidence: 60%
“…HIPS is formed by 6–15 wt % of a rubber dispersed in the form of particles into a polystyrene (PS) matrix where the dispersion is stabilized by the interfacial agent composed of a graft copolymer (rubber ‐g‐ PS) formed “ in situ” during the HIPS synthesis 2, 3. HIPS can be obtained by dissolving an appropriate amount of a rubber, usually polybutadiene (PB) or styrene–butadiene copolymers (SB or SBS), in styrene, followed by the in situ polymerization of the styrene monomer.…”
Section: Introductionmentioning
confidence: 99%
“…However, a single size distribution of very small particles makes the ABS resins stiff, glossy, and less tough, while big particles impair stiffness and gloss, but improve toughness. The optimum mean particle size for a combination of toughness, stiffness, and surface gloss is about 0.3-0.5 μm [206]. Gloss is largely dependent on particle size [207].…”
Section: Blends Of Polystyrene and Styrene Copolymersmentioning
confidence: 99%
“…The proportion of grafted SAN in the interface depends on the total amount of AN added and on the distribution of the grafted polymer between internal and external grafts. The proportion of graft copolymer included rises with increasing particle size and decreases with cross-link den sity [206]. Emulsion-grafted small particles exhibit a closed shell of graft copolymer on their surface.…”
Section: Blends Of Polystyrene and Styrene Copolymersmentioning
confidence: 99%